Coverings on Pitfall Traps Influence the Abundance of Ground-Dwelling Arthropods - Juraj Litavský; Pavol Prokop (Diversity, 2023)
Pitfall traps provide a cost-effective method of studying the diversity and abundance of ground-dwelling arthropods, such as beetles and spiders. Their efficiency depends on factors such as size, shape, and substances used to kill or preserve the specimens. Entomologists often employ covers on pitfall traps to prevent dilution of fixation liquids or keep the traps open. In this study, we investigated whether the presence or absence of covers, as well as their colour (black versus translucent), over pitfall traps has an impact on the species diversity and abundance of carabid beetles and harvestmen. These arthropods serve as common examples of ground-dwelling invertebrates, both in forest and meadow environments. Our findings revealed that traps with black-coloured coverings captured significantly higher numbers of beetles than translucent traps, but the uncovered traps were not significantly different from the two. The species richness tended to be highest in uncovered traps. The uncovered traps were the most efficient in capturing adult harvestmen, followed by translucent and black covers in terms of adult harvestmen abundance and diversity. In conclusion, the use of covers on pitfall traps significantly affects the estimates of arthropod abundance and should be taken into account in future research.